Ḵẖut̤ūt̤-i Akbar banām muṣavvir-i fit̤rat Ḥaz̤rat Maulānā Ḵẖvājah Ḥasan Niẓāmī, Dihlī - Akbar Allāhābādī, 1846-1921 (SAMP early 20th-century Indian books project, 1922)
Author's correspondence with Ḵẖvājah Ḥasan Niẓāmī Dihlavī, 1878-1957 Urdu writer.